The family Xeniidae (Octocorallia: Malacalcyonacea) of Vietnam with two new records - Hoang, Xuan Ben (Academia Journal of Biology, 2024)
Xeniidae is a soft coral family that has contributed to the diversity of tropical coral reef communities, including those found in Southeast Asia. From 50 soft coral samples of the family Xeniidae collected from coastal fringing reefs along the coast of central Vietnam, five species have been recorded belonging to two genera, Xenia (two species) and Heteroxenia (three species). Of five species, two were recorded for the first time in Vietnam are Xenia novaebritaniae Ashworth, 1900 and Heteroxenia elisabethae Kölliker, 1874. An identification key was provided based on colony forms and morphological characters of sclerites for five xeniid corals in Vietnam.